2022
DOI: 10.1136/bmj-2021-065846
|View full text |Cite
|
Sign up to set email alerts
|

Full endoscopic versus open discectomy for sciatica: randomised controlled non-inferiority trial

Abstract: Objective To assess whether percutaneous transforaminal endoscopic discectomy (PTED) is non-inferior to conventional open microdiscectomy in reduction of leg pain caused by lumbar disc herniation. Design Multicentre randomised controlled trial with non-inferiority design. Setting Four hospitals in the Netherlands. Participants 613 patients aged 18-70 years with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 45 publications
2
74
0
Order By: Relevance
“…The findings of the PTED study are expected to have implications, both for patients at an individual level as for society. At an individual level, it has been shown that PTED is non-inferior to open microdiscectomy in the treatment of leg pain and that PTED has more favourable patient-reported outcomes such as less low back pain, less functional disability due to low back pain and a higher health-related quality of life at 12 months after surgery 21. These differences in outcomes between PTED and open microdiscectomy, however, were relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the PTED study are expected to have implications, both for patients at an individual level as for society. At an individual level, it has been shown that PTED is non-inferior to open microdiscectomy in the treatment of leg pain and that PTED has more favourable patient-reported outcomes such as less low back pain, less functional disability due to low back pain and a higher health-related quality of life at 12 months after surgery 21. These differences in outcomes between PTED and open microdiscectomy, however, were relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…The PTED-study aimed to assess the effectiveness and cost-effectiveness (CE) of PTED compared with open microdiscectomy in patients with lumbar disc herniation 20. Results of the effectiveness analyses suggest that PTED is non–inferior to open microdiscectomy in leg pain reduction at 12 months after surgery 21. Furthermore, PTED had more favourable results for patient-reported leg pain and health-related quality of life as compared with open microdiscectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The step-by-step operative procedure of PCN has been published elsewhere. 12 In brief, PCN was performed under antibiotic prophylaxis and local anesthesia. After identifying the correct level of the cervical spine using fluoroscopy, an entry point for the needle was marked next to the medial part of the sternocleidomastoid muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional open lumbar surgery has been perceived as an effective intervention but carries several disadvantages, including postoperative back pain and a long recovery period. Subsequently, percutaneous endoscopic lumbar discectomy has been developed to facilitate lumbar discectomy 4 6 , with the following advantages such as paravertebral soft tissue protection, shorter hospital stays, less blood loss, and faster patient recovery 6 8 . Consequently, the percutaneous endoscopic technique received increasing attention from spinal surgeons around the worldwide 9 .…”
Section: Introductionmentioning
confidence: 99%